Influence of Bases and Ligands on the Outcome of the Cu(I)-Catalyzed Oxidative Homocoupling of Terminal Alkynes to 1,4-Disubstituted 1,3-Diynes Using Oxygen as an Oxidant - Adimurthy, Subbarayappa; Malakar, Chandi C; Beifuss, Uwe (Journal of organic chemistry, 2009)
The efficient Cu(I)-catalyzed oxidative homocoupling of terminal alkynes in the presence of a base using an amine as a ligand and oxygen as an oxidant yields the symmetrical 1,3-diynes with yields of up to 99%. The outcome of the couplings critically depends on the proper choice of base and ligand as well as reaction conditions. Best results were observed with 2.0 mol % CuCl, 1.5 mol % TMEDA or DBEDA, and DBU or DABCO in acetonitrile.